ABAE: Auxiliary Balanced AutoEncoder for class-imbalanced semi-supervised learning - Tang, Qianying; Wei, Xiang; Su, Qi; Zhang, Shunli (Pattern recognition letters, 2024)
Semi-supervised learning has achieved extraordinary success in prevalent image-classification benchmarks. However, a class-balanced distribution that differs notably from real-world data distribution is required. In general, models trained under class-imbalanced semi-supervised learning conditions are severely biased towards the majority classes. To address this issue, we propose a novel framework called ABAE by implanting an Auxiliary Balanced AutoEncoder branch into existing semi-supervised learning algorithms. Considering that adaptive feature augmentation for different classes can alleviate confirmation bias, we devise a class-aware reconstruction loss to train the AutoEncoder module. To further smooth the output, we adopt a graph-based label propagation scheme at the end of the AutoEncoder. Extensive experiments on CIFAR-10/100-LT, SVHN-LT and Small ImageNet-127 demonstrate the effectiveness of ABAE. •Propose an Auxiliary Balanced AutoEncoder branch(ABAE) with a class-aware reconstruction loss for CISSL.•Utilize the adaptive feature augmentation for different classes to alleviate the confirmation bias.•Adopt a graph-based label propagation scheme to smooth the output of the ABAE.•Demonstrate the effectiveness of the ABAE through experiments on various imbalanced datasets.